Financial Management in Islamic Boarding Schools (Pesantren) - Hamdana, Asrah Putri; Donna, Siti Rahma (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Islamic boarding schools (pesantren) play a significant role in Indonesia's education system, yet many face financial challenges due to limited and irregular funding sources. Effective and accountable financial management is essential for their sustainability and growth. Objective: This study aims to identify and examine the various funding sources utilized by Islamic boarding schools, including student fees, endowments (waqf), donations, grants, school-run businesses, and government assistance. Method: The research was conducted in 2024 using a descriptive qualitative method with a library research approach. Data were collected from scholarly journals and expert writings by identifying, categorizing, and critically analyzing relevant literature. The analysis involved qualitative descriptive techniques, theoretical comparison, synthesis, and comparative analysis. Result: The findings highlight the importance of strengthening budget planning, oversight, and evaluation within Islamic boarding schools. The implementation of Islamic accounting standards is recommended to enhance financial accountability and effectiveness in fund management. Conclusion: Islamic boarding schools must adopt structured financial planning and transparent management practices to ensure the optimal use of available resources. Attention to governance mechanisms is crucial for sustainability. Contribution:This study contributes to the literature by offering alternative, innovative, and sustainable fundraising strategies, such as Islamic investments and crowdfunding, to support the long-term financial stability of Islamic boarding schools.